Prevention of injuries of the anterior cruciate ligament in soccer players - Brito, J.; Soares, J.; Rebelo, A. N. (Revista Brasileira de Medicina do Esporte, 2009)
Knee injury is the commonest severe injury presented by football players and the anterior cruciate ligament appears as one of the most frequently injured knee ligaments. Thus, prevention of anterior cruciate ligament injuries must be a priority in soccer practice, regardless of the athletes' competitive level, age or sex. OBJECTIVES: the objective of this work is to analyze the importance of prevention of the anterior cruciate ligament injury in soccer players which can be incorporated in the training program. METHODOLOGY: the methodology used was a review of the literature. CONCLUSIONS: A program with three weekly sessions, composed by neuromuscular and proprioceptive training is proposed to prevent anterior cruciate ligament injuries in soccer players.